Problem gambling severity in a nationally representative sample of the Israeli population: the moderating role of ethnonational affiliation - Gavriel-Fried, Belle; Loewenthal, Amit; Vana, Noa (Frontiers in Public Health, 2023)
Introduction: Gambling is a public health concern. Problem gambling is related to a range of psycho-social risk factors including ethnonational affiliation. Israel is an insightful case to probe problem gambling, given the socio-economic marginalization of Israeli Arabs, the continued exposure of Israelis to stress and the conservative Israeli gambling market. This study aimed to estimate problem gambling severity in Israeli society, characterize the sociodemographic, environmental, mental health, and gambling-related risk factors associated with problem gambling severity, and examine the role of ethnonational affiliation (Israeli Jewish/Arab) as a moderating factor in the associations between these risk factors and problem gambling severity. Methods: A cross-sectional study based on a representative sample of 3,244 Israelis conducted in 2022, of whom 1,626 had gambled in the previous year. Measurements included Problem Gambling Severity Index, Gambling Behaviors, Perceived Neighborhood Cohesion, Stress, the Patient Health Questionnaire-4, and sociodemographic variables. Results: Low-risk, moderate-risk and problem gambling were reported by 16.7% of the total sample. The main risk factors for problem gambling were being an Israeli Arab, traditional, residing in a low socio-economic cluster, reporting anxiety symptoms, and higher gambling behaviors, specifically in legal/illegal online gambling. Ethnonational affiliation (Israeli Jewish/Arab) moderated the associations between gambling, illegal online gambling, and problem gambling severity. Higher neighborhood cohesion emerged as a risk factor for problem gambling solely for Israeli Arabs. Discussion: As an excluded minority, Israeli Arabs may turn to gambling as a method to access the core Republican community, thus, exposing themselves to a higher risk of developing problem gambling.